1-D photonic crystals for photovoltaics - Karasiński, Paweł; Gondek, Ewa (Photonics Letters of Poland, 2012)
The paper presents the theoretical analysis of photonic structures with 1-D photonic crystals on both sides of the slab glass and the results of experimental research. Within the scope of theoretical analysis, using the 2x2 transfer matrix method, we have determined the spectral reflectivity and transmittance characteristics, and basing on the said characteristics, we have determined the influence of the number of bilayers on the maximum reflectivity and on the width of the main reflectivity peak. For the structure with four bilayers (SiO2/TiO2) we have obtained the maximum reflectivity of 0.933 for the wavelength λr = 505nm and full width at half maximum of the main reflectivity peak of FWHM=185nm. Full Text: PDF References T.M.Razykov, C.S.Ferekides, D.Morel, E.Stefanakos, H.S.Ullal, H.M.Upadhyaya,"Solar photovoltaic electricity: Current status and future prospects", Sol. Energy 85, 1580 (2011)[CrossRef] B. Parida, S. Iniyanb, R. Goic,"A review of solar photovoltaic technologies", [CrossRef] Organic electronics, edited by Hagen Klauk, (Weinheim, WILEY-VCH Verlag GmbH & Co.KGaA,. 2006) E. Gondek, I.V.Kityk, A.Danel,"Some anthracene derivatives with N,N-dimethylamine moieties as materials for photovoltaic devices", [CrossRef] E.Gondek, Y.Djaoued, J.Robichaud, P.Karasiński, I.V.Kityk, A.Danel, K.J.Plucinski,"Influence of TiO2 nanoparticles on the photovoltaic efficiency of the ITO/PEDOT:PSS/fluorine copolymers/polythiophene: TiO2/Al architecture", J. Mater. Sci.: Mater Electron[CrossRef] R.Signerski, G.Jarosz,"Effect of buffer layers on performance of organic photovoltaic devices based on copper phthalocyanine-perylene dye heterojunction", Opto-Electron. Rev. 19, 468 (2011)[CrossRef] A.G.Imenes, D.R.Mills,"Spectral beam splitting technology for increased conversion efficiency in solar concentrating systems: a review", Sol. Energy Mater. Sol. Cells 84, 19 (2004)[CrossRef] A.Zhedi,"Review of modelling details in relation to low-concentration solar concentrating photovoltaic", Ren. Sust. Energy Rev 15, 1609 (2011)[CrossRef] B.C.Rowan, L.R.Wilson, B.S.Richards,"Advanced Material Concepts for Luminescent Solar Concentrators", [CrossRef] R.M.Almeida, L.M.Fortes, M.C.Gonçalves,"Sol–gel derived photonic bandgap coatings for solar control", Opt. Mater. 33, 1867 (2011)[CrossRef] E. Yablonovitch,"Inhibited Spontaneous Emission in Solid-State Physics and Electronics", Phys. Rev. Lett. 58, 2059 (1987)[CrossRef] G.V.Morozov, F.Placido, D.W.L.Sprung,"Absorptive photonic crystals in 1D", J. Opt. 13, 035102 (2011)[CrossRef] P.Karasiński, "Influence of aging and annealing on the properties of silica films produced with sol-gel method", Opt. Appl. 36, 389 (2006) P.Karasiński, E.Gondek, S.Drewniak, I.V.Kityk,"Nano-sized blue spectral shift in sol–gel derived mesoporous titania films", J. Sol Gel Sci. Techn. 61, 355 (2012)[CrossRef]